2009
DOI: 10.1128/jvi.01197-09
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Human Immunodeficiency Virus Type 1 Matrix Binding to Membranes and Nucleic Acids

Abstract: The human immunodeficiency virus type 1 (HIV-1) matrix (MA) protein targets HIV-1 precursor Gag (PrGag) proteins to assembly sites at plasma membrane (PM) sites that are enriched in cholesterol and phosphatidylinositol-(4,5)-bisphosphate [PI(4,5)P 2 ]. MA is myristoylated, which enhances membrane binding, and specifically binds PI(4,5)P 2 through headgroup and 2 acyl chain contacts. MA also binds nucleic acids, although the significance of this association with regard to the viral life cycle is unclear. We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

24
172
6
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 133 publications
(203 citation statements)
references
References 56 publications
(103 reference statements)
24
172
6
1
Order By: Relevance
“…Moreover, we have shown that RNA binding enhances the binding specificity of MA to PI(4,5)P 2 -containing membranes. This was evident by the fact that PI(4,5)P 2 -containing liposomes successfully competed with nucleic acids for MA binding, whereas other liposomes did not (32,33). In agreement with our results, RNase treatment of Gag synthesized in vitro using rabbit reticulocyte lysate significantly reduced the selectivity of Gag binding to PI(4,5)P 2 liposomes as opposed to phosphatidylserine-containing liposomes (34).…”
supporting
confidence: 81%
See 4 more Smart Citations
“…Moreover, we have shown that RNA binding enhances the binding specificity of MA to PI(4,5)P 2 -containing membranes. This was evident by the fact that PI(4,5)P 2 -containing liposomes successfully competed with nucleic acids for MA binding, whereas other liposomes did not (32,33). In agreement with our results, RNase treatment of Gag synthesized in vitro using rabbit reticulocyte lysate significantly reduced the selectivity of Gag binding to PI(4,5)P 2 liposomes as opposed to phosphatidylserine-containing liposomes (34).…”
supporting
confidence: 81%
“…NMR investigations have indi-cated that HIV-1 MA preferentially binds to soluble PI(4,5)P 2 mimics through contacts with the lipid headgroup and its 2Ј-acyl chain and that binding promotes both exposure of the MA myristate group and protein oligomerization (28,45). Consistent with the above observations, we have shown that MA proteins tend to organize as hexamers of trimers on lipid membranes containing PI(4,5)P 2 (51) and that the binding specificity of MA is enhanced by cholesterol (32,33).…”
supporting
confidence: 76%
See 3 more Smart Citations